THE ETHNIC CARD OF THE KARACHAYEVO-CHERKES REPUBLIC: THE SECOND HALF XX THE BEGINNING OF THE XXI CENTURY - Alexander Alexandrovich Cherkasov; Irina Vladimirovna Chernova (Наука. Инновации. Технологии)
Introduction: Karachay-Cherkessia is a type of regions in which there is an active change in the ethnic structure of the population. Over the past 50 years, there have been changes in proportions in the ethnic structure of the region's population, as well as changes in the geography of the resettlement of the titular ethnic groups of the republic. The purpose of the study is to conduct a comparative analysis of the resettlement of titular ethnic groups in Karachaevo-Cherkessia in the second half of the XX century and at the beginning of the 21st century. Materials and methods of research: author's GIS: "Mountainous settlement of the North Caucasus" and "Atlas Information System" Settlement of Peoples in Russia "were used. Cartographic methods and methods are applied as well as the method of statistical analysis, the Comparative method. The multiscale approach is the key, allowed to study the ethnic structure in general in the republic and at the level of individual municipalities. The results of the research and their discussion: the work details the resettlement of 5 titular ethnic groups of the Republic of Karachaevo-Cherkessia: Abazin, Karachais, Nogais, Russians, Circassians. The analysis is presented for the periods: Soviet from 1959 to 1989 and post-Soviet from 1989 to 2010. A significant place is given to the peculiarities of changing ethnic proportions at the level of municipal districts, as well as events and processes that to varying degrees contributed to a change in the ethnic structure of the population of the republic. The authors consider the features of the involvement of the titular ethnic groups of Karachay-Cherkessia in urbanization processes. The main conclusions and discussion: the authors made a number of conclusions, including that the ethnic structure of the population, and with it the geography of the settlement of ethnic groups in Karachaevo-Cherkessia during the second half of the XXth century beginning of the 21st century, changed under the influence of the growth (reduction) in the number of individual ethnic groups. The growth in numbers was due to active demographic processes, primarily among the Karachais, and to a lesser extent the Abazin, Circassians, and Nogais, against this background active migration processes - the departure of Russians outside the republic in the post-Soviet period inluenced their decline in numbers. Karachaevtsy quite actively expanded their settlement area, primarily due to the municipal districts, the compact residence of Russians. Circassians, Abazins and Nogais practically do not expand their settlement area; in the post-Soviet period, the Abazin and Nogai people have an increased concentration of populations in the settlements that make up the traditional area of their resettlement. At the present stage there is an active involvement of the titular ethnoses of the republic in urbanization processes.